Prevalence of Specific IgE to Dust and Storage Mites in Patients from Buildings with Moisture Damage Using Pharmacia- and DPC-Specific IgE Immunoglobulin Assays - Pennanen, Sirpa; Elg, Peter; Mussalo-Rauhamaa, Helena (Global Journal of Respiratory Care, 2018)
The interpretation of the results of in vitro tests for allergy to different kinds of mites may be challenging for clinicians due to the methodological differences between commercial tests. We assessed the presence of specific IgE-antibodies to house dust and storage mites in the serum of 24 patients with respiratory symptoms, and in 24 healthy controls, using two methods: the Pharmacia UniCAP System® (today Thermo Fisher Scientific. Allergy. Phadia AB) and DPC Alastat assays®. We also tested a storage mite mix reagent from Pharmacia. The presence and characterisation of the mites in the dust samples were assessed using microscopy. The Pharmacia experimental storage mite mix was positive for 11 out of 12 patients in a Pharmacia positive specific test. In the patient sera, Pharmacia detected 61 positive specific responses, whereas DPC detected 24. This indicates a significant analytical difference between the methods. The presence of identifiable mites or mite allergens in dust found by microscopy might confirm the IgE response. Combining the specific IgE test for the house mite Dermatophagoides pteronyssinus and a storage mite mix test, including the mites Acarus siro, Glycophagus domesticus, Lepidoglyphus destructor and Tyrophagus putrescentiae, can produce a cost-effective estimate of a suspected mite sensitisation case (IgE response).